Pelatihan Cultural Skills sebagai Upaya Memperkuat Interaksi Multikultural Santri di Pondok Pesantren Al-Kautsar Pamekasan - Ishlakhatus Sa’idah; Moh. Ziyadul Haq Annajih (Kanigara, 2025)
Islamic boarding schools are educational institutions with distinctive traditional and spiritual values. However, cultural diversity in the Islamic boarding school environment often becomes a challenge in creating social harmony. This activity aims to explore the effectiveness of cultural skills training in strengthening multicultural interactions at the Al-Kautsar Pamekasan Islamic Boarding School. The approach used was Participatory Action Research (PAR) and involved 25 students in a training program that lasted for three months. The results showed that this training succeeded in increasing participants' understanding of the importance of cultural diversity, strengthening cross-cultural communication skills and building an attitude of tolerance. Participants showed significant changes in social interactions including increased empathy and appreciation for different cultural perspectives. However, the application of these skills in a broader social context still faces challenges. Therefore, it can be concluded that cultural skills training is effective in supporting multicultural interactions in Islamic boarding schools, but requires follow-up to strengthen its impact outside the Islamic boarding school environment.